Developing a Green Corporate Image: An Achievement for Competitive Advantage through Organizational Culture and Green Marketing Strategy - Widyastuti, Sri (2019)
This study aims to provide an analysis on the development of green marketing strategy and its relationship towards organizational culture and competitive advantage. An insight into the importance of green corporate image, green marketing strategy and their effect on the company's competitive advantage will also be investigated. Nowadays, society desires business corporations to contribute more on green issues and offer solutions on the environmental problems facing by local community. Previous studies have found that business corporations that able to integrate strategic action between economic objective and green/environmental friendly action will survive and gain competitive advantage. Self-administered survey questionnaires were distributed to employees in manufacturing and service industry. Then, statistical analyses were carried out to answer research objectives of this study. The results indicate that green marketing strategy and organizational culture give a positive green corporate image and create greater competitive advantage in the industry.